Second generation modifiers of colistin resistance show enhanced activity and lower inherent toxicity. Issue 25 (23rd June 2016) - Brackett, Christopher M.; Furlani, Robert E.; Anderson, Ryan G.; Krishnamurthy, Aparna; Melander, Roberta J.; Moskowitz, Samuel M.; Ernst, Robert K.; Melander, Christian
Abstract: We recently reported a 2-aminoimidazole-based antibiotic adjuvant that reverses colistin resistance in two species of Gram-negative bacteria. Mechanistic studies in Acinetobacter baumannii demonstrated that this compound downregulated the PmrAB two-component system and abolished a lipid A modification that is required for colistin resistance. We now report the synthesis and evaluation of two separate libraries of substituted 2-aminoimidazole analogues based on this parent compound. From these libraries, a new small molecule was identified that lowers the minimum inhibitory concentration of colistin by up to 32-fold greater than the parent compound while also displaying less inherent bacterial toxicity, thereby minimizing the likelihood of resistance evolution. Graphical abstract: